Quantitative computed tomography detects interstitial lung diseases proven by biopsy - Ariani, Alarico; Imperatori, Andrea; Castiglioni, Massimo; Daffrè, Elisa; Aiello, Marina; Bertorelli, Giuseppina; Chetta, Alfredo; Dominioni, Lorenzo; Rotolo, Nicola (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: The Quantitative chest CT (QCT) is emerging as a promising tool in the assessment of interstitial lung disease (ILD). However, the precise relationship between QCT parameters and the fibrosis detectable in lung tissue, remains to be established. Objectives: The aim of this study was to compare QCT and histopathological features in patients with ILD. Moreover we verified if the QCT assessment is similar in patients with or without a ILD diagnosis proven by a biopsy. Methods: Twenty patients affected by ILD who underwent a chest CT and, later, a lung biopsy, were enrolled. Patients were divided according to the histopathological findings (IPF vs sarcoidosis) in two groups (respectively bIPF and bSarc). Other 20 patients with a radiological diagnosis of IPF were included in a control group (rIPF). All CTs were post-processed with a free software (Horos) in order to obtain an ILD quantitative assessment. Results: There were no differences in terms of gender, smoking habit and spirometric values between patients’ groups. rIPF subjects were older than the other: 70 vs 59 and 47 years (p